2016
DOI: 10.1515/noise-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the understanding of soundscape: objective variables and objectifiable criteria that predict acoustic comfort in urban places

Abstract: The overall aim of this research was to find a group of easy-to-access variables, that are measurable or assessable, and which help predict acoustic comfort in urban places, in order to make further progress in developing a soundscape indicator based on indices readily available in urban environments. Our main conceptual framework has been the Environmental Experience Model and the ISO of Soundscape, together with the most up-to-date information and technology, where parameters that influence the soundscape an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 3 publications
1
35
0
3
Order By: Relevance
“…The results presented in this paper are similar to those found in the previous study conducted in Vitoria-Gasteiz [23], with the percentage of explained variance also being similar (32% and 36%, respectively). In both studies, it was concluded that the most significant aspect in soundscape pleasantness is the congruence between soundscape and landscape.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results presented in this paper are similar to those found in the previous study conducted in Vitoria-Gasteiz [23], with the percentage of explained variance also being similar (32% and 36%, respectively). In both studies, it was concluded that the most significant aspect in soundscape pleasantness is the congruence between soundscape and landscape.…”
Section: Discussionsupporting
confidence: 90%
“…In a similar vein, a recent publication [23] explores the significance of a wide range of acoustic and non-acoustic factors in the soundscape of several public urban spaces in the city of Vitoria-Gasteiz (Spain). This work shows that the variable which best explains soundscape is the congruence between soundscape and landscape as perceived by the user of the place.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, urban sounds cannot be captured at scale and, consequently, they are not considered when planning cities [ 20 ]. That is because the collection of data for managing urban acoustic environments has mainly been relegated to small-scale surveys [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the process of environmental experience, Herranz-Pascual et al have been developing work in the soundscape field following this approach, proposing a model of environmental experience for studying soundscape, based in the psychological process of environmental experience [32,34,35,36]. This model comprises three fundamental aspects: Person , Activity, and Place .…”
Section: Introductionmentioning
confidence: 99%
“…), so it is necessary to determine which variables are the most influential in the environmental sound experience, as well as establishing processes and procedures for this type of analysis. Currently, most studies in this field focus on the influence of alternative stimuli to sound [35,37,38,39,40,41,42,43], detecting that one of the most influential stimulus in the perception of the acoustic environment is the vision. With regard to the study of contextual elements related to the Person-Place Interaction , reference is made in the cross-national comparison in assessment of urban park soundscapes, in the analysis and assessment of soundscapes in commonly used sightseeing sites (comparison between tourists and non-tourists), as well as comparison between responses of experts and non-experts [27,44,45,46].…”
Section: Introductionmentioning
confidence: 99%